Privatization and revolution: a critical reading of the Omar Effendi case - El Hadidi, Ahmed (AUC Knowledge Fountain, 2012)
Privatization is a program first applied in Britain to reform the public sector, mainly to decrease its burden on government spending. Although many countries have successfully followed suit, such as Brazil, such was not the case in Egypt. This failure has become even more apparent after the 25 January Revolution in 2011, in the wake of which many Egyptian citizens and workers filed cases against entities responsible for various public sector projects. One such entity was the Omar Effendi Company, which was purchased by the Saudi Anwal Company in 2008. In 2010, a case was filed against the buyer before the Administrative Court, claiming that the contract for the sale of Omar Effendi was null and void. While the Court concurred with this claim, its decision was criticized on several grounds: competence; arbitrability, specially that previous arbitral award regarding the same issue had been handed; and, that the contract imposed illegal obligations on the buyer. Through a critical reading of the Omar Effendi case materials, including party memoranda and supporting documents, this thesis argues that the Administrative Court judgment was in violation of the law.